A Novel Peripheral Action of PICK1 Inhibition in Inflammatory Pain - Jensen, Kathrine Louise; Noes-Holt, Gith; Sørensen, Andreas Toft; Madsen, Kenneth Lindegaard (Frontiers in Cellular Neuroscience, 2021)
Chronic pain is a major healthcare problem that impacts one in five adults across the globe. Current treatment is compromised by dose-limiting side-effects including drowsiness, apathy, fatigue, loss of ability to function socially and professionally as well as a high abuse liability. Most of these side-effects result from broad suppression of excitatory neurotransmission. Chronic pain states are associated with specific changes in the efficacy of synaptic transmission in the pain pathways leading to amplification of non-noxious stimuli and spontaneous pain. Consequently, a reversal of these specific changes may pave the way for development of efficacious pain treatment with fewer side-effects. We have recently described a high-affinity, bivalent peptide TAT-P4-(C5)2, enabling efficient targeting of the neuronal scaffold protein, PICK1, a key protein in mediating chronic pain sensitization. In the present study, we demonstrate that in an inflammatory pain model, the peptide does not only relieve mechanical allodynia by targeting PICK1 involved in central sensitization, but also by peripheral actions in the inflamed paw. Further, we assess effects of the peptide on novelty-induced locomotor activity, abuse liability and memory performance without identifying significant side-effects.